2023
DOI: 10.7759/cureus.34789
|View full text |Cite
|
Sign up to set email alerts
|

Confusion With Presentations of Calcium Pyrophosphate Dihydrate Disease: A Report of Two Cases Mistaken for Cellulitis

Abstract: Both pseudogout and cellulitis are diseases that may mimic one another in clinical practice. We discuss two cases of acute calcium pyrophosphate dihydrate (CPPD) arthritis mistaken for cellulitis in the emergency department. Both patients experienced significant improvement after management was changed to treat CPPD. These cases highlight how it is essential for physicians to consider CPPD as a differential diagnosis for a patient that is presenting with signs of inflammation in any joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…A nal diagnosis of acute chondrocalcinosis was made by the visualization of positive birefringent rhomboid-shaped crystals in the wrist joint synovial uid. Masooma et al [7] reported two cases of acute calcium pyrophosphate dihydrate arthritis mistaken for cellulitis. In our patient, based on clinical signs and symptoms, previous history of the left forearm with hand swelling (the speci c details are unknown), and laboratory parameters, an initial diagnosis of hand cellulitis was made.…”
Section: Discussionmentioning
confidence: 99%
“…A nal diagnosis of acute chondrocalcinosis was made by the visualization of positive birefringent rhomboid-shaped crystals in the wrist joint synovial uid. Masooma et al [7] reported two cases of acute calcium pyrophosphate dihydrate arthritis mistaken for cellulitis. In our patient, based on clinical signs and symptoms, previous history of the left forearm with hand swelling (the speci c details are unknown), and laboratory parameters, an initial diagnosis of hand cellulitis was made.…”
Section: Discussionmentioning
confidence: 99%